Implementasi Topsis Pada Sistem Rekomendasi Tempat Wisata Pantai Di Sekitar Malang Berbasis Lokasi - Muhamad Hilmi Hibatullah; Ratih Kartika Dewi; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The tourism sector in Indonesia currently considered to be an effective role in increasing the country's foreign exchange. In 2016, the tourism sector was the second largest constributor to foreign exchange in the amount of USD12.5 billion. Malang is one of the areas that have a lot of potential tourism object. Beach tourism in Malang is a lot where it is cause visitors confused to choose the beach to be visited. This research propose to make a beach recommendation system around Malang by applying the Technique For Order Preference by Similiarity to Ideal Solution (TOPSIS) method. The TOPSIS method was chosen because TOPSIS was able to do the selected alternative ranking, where the selected alternative had the closest distance from the positive ideal solution and the farthest distance from the negative ideal solution. The criteria used in this system are distance, cost, rating, facilities and transportation. System functional testing shows that 100% of the functionality is valid. Furthermore, testing the validation of the algorithm, obtained the results 100% of similarities between the system output and manual calculation. While rank consistency testing obtained results that show that the TOPSIS method has a good level of consistency when implemented on the beach recommendation system